Driving sustainability: IoT sensor integration for efficient car AC control - Gudapalli Karuna; Md Amruth Pasha; Yagateela Sree Ohm; Gongati Ashish; Mundher Adnan Myasar; R J Anandhi; Jain Alok; Kumar Ashwani (E3S Web of Conferences, 2024)
The Car AC Control Using IoT Sensor. The interior temperature of the car rapidly increases mostly during the hot summer months. This paper aims to address the challenge of maintaining a comfortable interior temperature in car, especially during hot summer months. To overcome this problem a mobile application is developed which helps to monitor the temperature in the car by using the Internet of Things (IoT). With this application the AC can be switched ON before getting into the car as the AC controller is linked to the mobile application. To power the system, a lithium-ion battery is used, which is recharged by the conversion of kinetic energy generated by the vehicle's movement, particularly from the wingtips. The intelligent design of air conditioners will ensures the efficient energy consumption with which the battery life can be prolonged. The proposed method will monitor the temperature inside the car.